Effectiveness of the dialectical behavior therapy skills training on emotion regulation of aggressive girls - Fatemeh Gholipoor-bazkiaghurab; Fatemeh Golshani; Farnaz Keshavarzi-arshadi; Sozan Emamipour; Mojghan Sepahmansour (فصلنامه ابن سینا)
Background: Given the harmful consequences of aggression on adolescents and those around them, this research was performed with the aim of evaluating the effectiveness of the dialectical behavior therapy skills training on emotion regulation of female aggressive students. Materials and methods: This study was a clinical trial with pre-test, post-test, and a 2-month follow-up on 24 female students. The sampling method was purposeful. For this goal, a call was sent to second-level secondary school counsellors to refer the female students who are studying in the second and third bases and are suspected of aggression. For collecting data, the Difficulties in Emotion Regulation Scale (DERS) developed by Gratz and Roemer and Bass and Perry Aggression Questionnaire were used. From the students referred to the education counselling center in Lahijan City, 24 subjects who had aggression disorder, a score lower than 69.99, were selected, and then they were assigned randomly into control and experimental groups The experimental group underwent 14 sessions of the dialectical behavior therapy skills training and the control group was registered in the waiting list. Results: The results of data analysis showed that there is not a significant difference between the mean difficulty scores of emotion regulation of aggressive girls who received the dialectical behavior therapy skills training and those of aggressive girls who didn’t receive this method (p<0.05). Conclusion: This research showed that although the skill-training of dialectical behaviour therapy reduces the difficulty emotion regulation of aggressive girls, but this amount is not statistically significant.